Virtual COVID-19 Clinical Teaching Session:: A Substitute for ‘Sheltered in Place’ MedicalStudents (Translation: The University of Toledo Journal of Medical Sciences, 2020)
The novel SARS-CoV-2 virus, or COVID-19, has caused a pandemic in the past year that has significantly impacted the health care system and medical education. This virus has uniquely impacted Emergency Medicine, as many COVID-19 patients suffer from acute respiratory distress or failure and require emergent stabilization. While physicians, residents, and medical students would all benefit from hands-on training on the medical management and stabilization of COVID-19 patients, this is not feasible due to risk of transmission and spread of the virus. Students have missed countless hours of hands-on clinical education because of the shift to online learning or emergency remote learning due to these concerns. A PowerPoint presentation was given via Webex by Emergency Medicine physicians and residents to medical students in hopes of bridging this gap. The lecture presented information on diagnosis, clinical management, and clinical course of COVID-19 positive patients in the Emergency Department. Students were able to engage with Emergency Medicine physicians and ask questions in real time. A pre-session survey and post-session survey were administered via Google Forms to assess students’ confidence in six different domains. There was significant improvement in all six domains of the survey when comparing the pre-session and post-session survey confidence intervals with a p
Keywords: Virtual; COVID-19; Emergency Department; Medical Student; Pandemic